PRESERVING AND TRANSMITTING CUSTOMS IN RURAL COMMUNITIES (PANGEEA, 2025)
In order to know the customs in all aspects, it is required to know the place and conditions in which they appear, to research all the customs concretely and thoroughly and then to relate it to similar customs in other areas of folklore, to the whole category of facts that that it belongs in our folklore and other peoples' folklore. In rural communities, customs gave life its own rhythm. Respecting and practicing them according to the ancestral order, gives a certain cadence to the collective life, the family and, in general, to the social life of the village. During agricultural work, habits established a certain balance between work and rest, through the stages that marked the end of some work and preparation for others. Even during a work day, during mowing or reaping, breakfast and lunch are strictly respected, along with a rest period after lunch, in which people sing and tell stories, and dinner.
Keywords: custom; tradition; rural community; folklore; rural culture